Ceramic based electronic component as retrospective radiation dosimeter. (April 2021) - Jakathamani, S.; Annalakshmi, O.; Jose, M.T.; Mathiyarasu, R.; Venkatraman, B.
Abstract: Surface mount electronic devices (like resistors, capacitors, and inductors) extracted from the portable electronic devices (mobile phones, USB drives, etc.) have been studied for dose reconstruction using luminescence techniques for radiological or nuclear emergencies. In this work, carbon coated ceramic resistors removed from the electronic instruments are analyzed using thermo luminescence (TL) technique for the retrospective dose reconstruction. TL measurements on beta irradiated ceramic resistors exhibited one major dosimetric peak at around 540 K in addition to three other low temperature peaks. A linear beta dose response has been observed from 1 Gy to 125 Gy with Minimum Detectable Dose (MDD) of 0.1 Gy. The dose response is found to be supralinear below 1 Gy. The fading studies have been carried out and investigated up to 30 days. The important kinetic parameters for the material like TL trap depth, frequency factor and order of kinetics are evaluated by deconvolution method. Highlights: Ceramic resister is useful for retrospective dosimeter based on TL. Minimum Detectable Dose by TL method is 0.1 Gy. TL dose response supralinear below 1 Gy and linear in1 Gy to 125 Gy.